Conjugate addition of nitrogen nucleophiles to an alpha,beta-unsaturated pyrrolidinone - Chan, P; Cottrell, I; Moloney, M (1997)
The conjugate addition of nitrogen nucleophiles to α,β-unsaturated lactam 1b under very mild conditions occurs in good yield with high diastereoselectivity. Deprotection provides a simple access to β-aminopyrrolidinones in excellent overall yield.